A Feasibility Study to Measure Protection Offered by a Coronavirus Disease 2019 Intubation Enclosure. Issue 1 (January 2022) - Diaz, Maria Carmen G.; Rahman, Tariq; Hossain, Jobayer; Dawson, Kimberly; Madaus, Stacy; Lim, Doyle
Abstract : This study assessed the feasibility of quantifying an intubation enclosure's ability to limit spread of aerosolized particles during simulated pediatric endotracheal intubation. Aerosolized particle counts were measured at the airway provider and around the room using the enclosure without suction, with suction, and no enclosure. The enclosure with suction had the least overall mean of 0.3-μ particles at the airway provider at 30 seconds (1, 396.0), followed by enclosure without suction (26, 308.3) and no enclosure (103, 517.3), P = .064. This study's intubation enclosure limited the spread of aerosolized particles. Additional studies are needed to ensure this model translates to actual patient care.